DAMGO in the central amygdala alleviates the affective dimension of pain in a rat model of inflammatory hyperalgesia - Zhang, Rui-Xin (2013)
Pain has sensory-discriminative and emotional-affective dimensions. Recent studies show that the affective component can be assessed with a conditioned place avoidance (CPA) test. We hypothesized that systemic morphine before a post-conditioning test would more potently attenuate the affective aspect compared to the sensory component and that DAMGO, a μ-selective opioid receptor agonist, injected into the central nucleus of the amygdala (CeA) would reduce established CPA. A rat model of inflammatory pain, produced by a complete Freund adjuvant (CFA) injection into the hind paw, was combined with a CPA test. Three experiments were performed on adult male Sprague-Dawley rats. Systemic morphine (0.5 or 1.0 mg/kg) in Experiment 1, intrathecal (i.t.) morphine (2.5 μg/rat) in Experiment 2, and intra-CeA DAMGO (7.7-15.4 ng/0.4μl) in Experiment 3 were given to CFA-injected rats (n=6-8/group) prior to a post-conditioning test. Saline-injected rats were used as control. Time spent in a pain-paired compartment was recorded twice, before conditioning and after a post-conditioning test. Paw withdrawal latency (PWL) to a noxious thermal stimulus was measured before experiment at day −1 and after the post-conditioning test; hyperalgesia was defined as a decrease in PWL. The data showed that CFA-injected rats had significantly negative CPA compared to those of saline-injected rats (P<0.05). Low dosage systemic morphine significantly (P<0.05) reduced CFA-induced CPA but had no effect on PWL. I.t. morphine did not inhibit the display of CPA but significantly increased PWL, suppressing hyperalgesia (P<0.05). Intra-CeA DAMGO significantly inhibited the display of CPA compared to saline (P<0.05) but had no effect on PWL. The data demonstrates that morphine attenuates the affective component more powerfully than it does the sensory and suggests that the sensory and the emotional-affective dimensions are underpinned by different mechanisms.